2003
DOI: 10.1002/art.10926
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for aerobic insufficiency in women with systemic lupus erythematosus

Abstract: Objective. To determine if fatigue is associated with diminished aerobic capacity in women with systemic lupus erythematosus (SLE). Methods. Eighteen women (age 35 ؎ 9 years) with mild SLE (Systemic Lupus Activity Measure ‫؍‬ 3.1 ؎ 2.1) and 16 healthy but sedentary controls (age 38 ؎ 8 years) completed peak treadmill exercise tests to determine aerobic capacity and Fatigue Severity Scales to quantify the severity of fatigue. Measures of oxygen consumption (VO 2 ) were recorded during the treadmill tests. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 15 publications
5
74
0
3
Order By: Relevance
“…Aerobic capacity is reduced to a level that is inadequate for avoiding fatigue while engaging in routine daily tasks. 8 However, the molecular mechanisms underlying reduced aerobic capacity are not understood. There is little data regarding the physiologic basis for the abnormal cardio-respiratory response and diminished exercise tolerance demonstrated by SLE subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic capacity is reduced to a level that is inadequate for avoiding fatigue while engaging in routine daily tasks. 8 However, the molecular mechanisms underlying reduced aerobic capacity are not understood. There is little data regarding the physiologic basis for the abnormal cardio-respiratory response and diminished exercise tolerance demonstrated by SLE subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in 50-90% of patients with SLE (5-8) and such patients reportedly have more fatigue than healthy people do (9)(10)(11)(12)(13)(14). As fatigue influences quality of life (13), it is an important variable to assess in treatment interventions.…”
mentioning
confidence: 97%
“…There is a growing body of evidence indicating impaired aerobic capacity in SLE patients [4][5][6][7]. For instance, Keyser et al [5] Additionally, Robb-Nicholson et al [18] showed that SLE patients performed at 45% of expected VO 2max , while Tench et al [19] concluded that SLE women exhibited poor exercise capacity, having a VO 2max 62% of the average expected value in healthy females of the same age (normality>85% VO 2max predicted) ( Furthermore, in a more recent study on childhood-onset SLE, Prado et al [22] observed both lower exercise tolerance and aerobic capacity when compared with healthy control children.…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 99%
“…For instance, Keyser et al [5] Additionally, Robb-Nicholson et al [18] showed that SLE patients performed at 45% of expected VO 2max , while Tench et al [19] concluded that SLE women exhibited poor exercise capacity, having a VO 2max 62% of the average expected value in healthy females of the same age (normality>85% VO 2max predicted) ( Furthermore, in a more recent study on childhood-onset SLE, Prado et al [22] observed both lower exercise tolerance and aerobic capacity when compared with healthy control children. Taken together, these findings suggest that the aerobic capacity impairment observed in SLE patients may be associated with a reduced capacity to engage in both daily occupational activities and recreational tasks.…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 99%
See 1 more Smart Citation